56.0k views
2 votes
Factor completely
3x^2+2x-1

User Istrebitel
by
4.9k points

2 Answers

3 votes

Answer:

(3x-1)(x+1)

Explanation:

I like to factor by grouping.

a=3

b=2

c=-1

To get those values I compared 3x^2+2x-1 to ax^2+bx+c.

Now our objective to help us factor this is: Find two integers that multiply to be a*c and add up to be b.

a*c=3(-1)

b=2

Guess what? Our numbers are already visible to us; that doesn't always happen. However, a*c=3(-1) and b=2=3+(-1).

So we are going to replace our 2x with 3x+-1x or -1x+3x. Either one is fine; they are the same thing.

3x^2+2x-1

Replacing 2x with -1x+3x.

3x^2-1x+3x-1

Grouping first 2 terms together and grouping 2nd 2 terms together.

(3x^2-1x)+(3x-1)

Now we are going to factor each grouping.

x(3x-1)+1(3x-1)

Now notice we have two terms here x(3x-1) and 1(3x-1). Both of these terms have a common factor of (3x-1). We are going to now factor out (3x-1).

(3x-1)(x+1)

User Rotsor
by
4.4k points
0 votes

Answer:


3x^2 + 2x - 1 = 3(x-(1)/(3))(x+1)

Explanation:

User Jafoor
by
4.1k points